Growth of selected probiotic strains with fructans from different sources relating to degree of polymerization and structure. (June 2016) - Mueller, Monika; Reiner, Jacqueline; Fleischhacker, Lisa; Viernstein, Helmut; Loeppert, Renate; Praznik, Werner
Highlights: The prebiotic effect of fructans was higher the lower the degree of polymerization (dp). Branched agave fructans induced growth faster than linear chicory fructans. The faster induction of branched fructans was also found at higher dp. The degradation patterns for linear and branched fructans were similar. Abstract: Fructans as prebiotics are an important factor in the functional food industry due to their beneficial effect on health. However, the influence of structure and degree of polymerization (dp) on their prebiotic effect is not fully elucidated so far. Unbranched inulin-type (β-2, 1 linked) fructans from chicory and branched mixed-type (β-2, 1 and β-2, 6 linked) fructans from agaves were separated into fractions with different dps using preparative size exclusion chromatography, and the growth curves of selected probiotic strains were determined. All fructans exerted a significant growth enhancement, being higher with lower dp and with branching. Lactobacillus acidophilus and L. paracasei CRL431 quickly used fractions independent of the dp, whereas other strains (i.e. L. reuteri ) did not use or only slowly used high dp fractions. Most strains cleaved fructans into smaller units before uptake into the cells. Our findings may contribute significantly to the development of improved prebiotic formulations.